Amino acids and peptides - Feigenson, Gerald W. (Henry Stewart Talks, 2019)
Ionisable groups, Amino acid properties, Amino acid classification, Peptides, Hydrophobic interactions, Myoglobin
Reviewed at 2022/11/27